2000
DOI: 10.1590/s0001-37652000000200007
|View full text |Cite
|
Sign up to set email alerts
|

A possible chelonian egg from the Brazilian late cretaceous

Abstract: This paper describes a possible fossil egg proceeding from the Bauru Group, Late Cretaceous of Paraná Basin, Brazil. External morphology, dimensions, texture and shell ornamentation examined under electron microscopy show close resemblance to the Recent podocnemidid chelonian eggs. Association with bony material in the outcrop suggests that it is related to a species of Podocnemis. Computerized tomography reveals a high density outer region corresponding to the shell component layers, and successive layers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
0
19
0
4
Order By: Relevance
“…Many authors have attempted to identify the species of turtle that potentially laid a given fossil egg (Gergens 1860;Meyer 1860;Hummel 1929;Kohring 1993;Gaffney 1996;Azevedo et al 2000).…”
Section: Taxonomic Assignment Of Fossil Turtle Eggsmentioning
confidence: 99%
“…Many authors have attempted to identify the species of turtle that potentially laid a given fossil egg (Gergens 1860;Meyer 1860;Hummel 1929;Kohring 1993;Gaffney 1996;Azevedo et al 2000).…”
Section: Taxonomic Assignment Of Fossil Turtle Eggsmentioning
confidence: 99%
“…The Malagasy eggs are only the fifth documented occurrence of Mesozoic turtle eggs from Gondwanan continents, following two specimens from Brazil (Azevedo et al, 2000;Marsola et al, 2014) and two from India (Sahni, 1957;Mohabey, 1998). The specimens described by Azevedo et al (2000) and Sahni (1957) were identified only by gross morphology, however, and microstructural analysis was not performed.…”
Section: Malagasy Turtlesmentioning
confidence: 99%
“…The specimens described by Azevedo et al (2000) and Sahni (1957) were identified only by gross morphology, however, and microstructural analysis was not performed. Additionally, many have questioned a turtle origin for the specimens described by Mohabey (1998) because of low-quality figures and the identification of a mammillary layer at the basal-most portion of the eggshell (Kohring, 1999;Jackson et al, 2008;Knell et al, 2011).…”
Section: Malagasy Turtlesmentioning
confidence: 99%
“…Clutches of small eggs have been referred to podocnemidid (Azevedo et al, 2000) and crocodilians (Magalhães-Ribeiro and Souto, 1999). The Adamantina Formation has yielded the only snake remains from the Cretaceous of Brazil.…”
Section: Adamantina Formationmentioning
confidence: 99%